2024
DOI: 10.1590/1519-6984.255692
|View full text |Cite
|
Sign up to set email alerts
|

Protease production and molecular characterization of a protease dipeptidyl-aminopeptidase gene from different strains of Sordaria fimicola

Abstract: The current research was designed to reach extracellular protease production potential in different strains of Sordaria fimicola which were previously obtained from Dr. Lamb (Imperial College, London) from North Facing Slope and South Facing Slope of Evolution Canyon. After initial and secondary screening, two hyper-producers strains S2 and N6 were selected for submerged fermentation and cultural conditions including temperature, pH, incubation period, inoculum size, substrate concentration, and different carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Optimization studies of Bacillus infantis SKS1 by Saggu and Mishra [36] also reported a substrate concentration of 1% for maximum protease production. In addition, strains of S. fimicola S2 and N6, as reported by Naureena et al [41] enhanced protease production by 1% casein concentration with a corresponding activity of 1.230 U/mL and 1.034 U/mL, respectively.…”
Section: Substrate Concentrationmentioning
confidence: 57%
“…Optimization studies of Bacillus infantis SKS1 by Saggu and Mishra [36] also reported a substrate concentration of 1% for maximum protease production. In addition, strains of S. fimicola S2 and N6, as reported by Naureena et al [41] enhanced protease production by 1% casein concentration with a corresponding activity of 1.230 U/mL and 1.034 U/mL, respectively.…”
Section: Substrate Concentrationmentioning
confidence: 57%
“…These enzymes can be found in all living beings, since they are necessary in several biological processes, playing key roles in the degradation of specific proteins. Furthermore, proteolytic enzymes can be applied in different industrial processes, such as in the detergent, food and pharmaceutical industries (Naureen et al, 2022;Solanki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%